The Future of Antarctica: Scenarios from Classical Geopolitics - Jeffrey McGee; D Edmiston; Marcus Haward (2022)
Antarctica is a magnificent place, a vast area of the planet that has been free from large-scale nation-state conflict from the advent of the age of exploration, when pioneers like Amundsen, Bellingshausen, Byrd, Mawson, Scott, Shackleton and Shirase arrived, to the present day. When the Cold War threatened to extend global tensions to this region, twelve nations negotiated the Antarctic Treaty of 1959, effectively setting aside differences over territorial claims and preventing militarization over a significant part of the globe. Over time, with participation of many more states, additional instruments covering environmental protection and marine conservation were added to create the Antarctic Treaty System. The intention by these states was to establish a “natural reserve, devoted to peace and science”, and as a general proposition, the Treaty System has been successful and that vision has been achieved.